Heteroepitaxial growth of tetragonal Mn2.7-xFexGa1.3 (0 ≤ x ≤ 1.2) Heusler films with perpendicular magnetic anisotropy - Kalache, Adel; Markou, Anastasios; Selle, Susanne; Hoeche, Thomas; Sahoo, Roshnee; Fecher, Gerhard H.; Felser, Claudia (APL Materials, 2017)
This work reports on the structural and magnetic properties of Mn2.7-xFexGa1.3 Heusler films with different Fe content x (0 ≤ x ≤ 1.2). The films were deposited heteroepitaxially on MgO single crystal substrates, by magnetron sputtering. Mn2.7-xFexGa1.3 films with the thickness of 35 nm were crystallized in a tetragonal D022 structure with (001) preferred orientation. Tunable magnetic properties were achieved by changing the Fe content x. Mn2.7-xFexGa1.3 thin films exhibit high uniaxial anisotropy Ku ≥ 1.4 MJ/m3, coercivity from 0.95 to 0.31 T, and saturation magnetization from 290 to 570 kA/m. The film with Mn1.6Fe1.1Ga1.3 composition shows high Ku of 1.47 MJ/m3 and energy product (BH)max of 37 kJ/m3 at room temperature. These findings demonstrate that Mn2.7-xFexGa1.3 films have promising properties for mid-range permanent magnet and spintronic applications.
CRIS-Team Scopus Importer:2022-04-14